Bleeding and Thrombotic Complications in the Use of Extracorporeal Membrane Oxygenation - Thomas, James; Kostousov, Vadim; Teruya, Jun (Seminars in Thrombosis and Hemostasis, 2018)
Extracorporeal membrane oxygenation (ECMO) has been used for >40 years to support lung and heart failure; however, bleeding and thrombosis remain serious complications. The known etiologies of bleeding include heparin effect or overdose, coagulopathy, thrombocytopenia, platelet dysfunction, acquired von Willebrand syndrome, and hyperfibrinolysis. Bleeding sites may include cannula insertion sites, recent surgical incisions, vascular access sites, lung, gastrointestinal tract, mouth, nose, thoracic cavity, abdominal cavity, and brain. Massive bleeding in the brain, the most feared bleeding complication, can be rapidly fatal because it occurs in a rigid closed space, is difficult to drain, and cannot be stopped with direct pressure to the bleeding site. Pulmonary hemorrhage may cause irreversible lung damage. Management should be swift and precise to prevent fatal bleeding. In contrast, etiologies of thrombosis include high fibrinogen and factor VIII levels, heparin resistance, and platelet activation. Achieving the optimal anticoagulation balance to prevent bleeding and thrombosis in ECMO patients is extremely complex. Experts in hemostasis should be a part of an institutional ECMO team and continuously available for immediate management.
Keywords: extracorporeal membrane oxygenation; ECMO; hyperfibrinolysis; heparin; hemolysis; acquired von Willebrand syndrome; bivalirudin